2003
DOI: 10.1182/asheducation-2003.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin’s Lymphoma: Biology and Treatment Strategies for Primary, Refractory, and Relapsed Disease

Abstract: Hodgkin's lymphomas belong to the most curable tumor diseases in adults. About 80% of patients in all anatomical stages and of all histological subtypes can be cured with modern treatment strategies. In spite of the great clinical progress, the pathogenesis of this peculiar lymphoproliferative entity has not been elucidated completely up until now.In In Section III, Dr. Connors states that fortunately there is a considerably decreased need for salvage strategies in Hodgkin's lymphomas since primary treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 115 publications
(34 reference statements)
0
92
0
5
Order By: Relevance
“…3 Hodgkin's lymphoma is a curable neoplasm given that, after a minimum follow-up of 6 years, more than 90% of patients are still alive and 80% are considered cured. 4 These rewarding results have been obtained by a combination of factors influencing treatment outcome in different ways. These factors can be briefly summarized as: (i) increasing accuracy of staging procedures; (ii) different treatment strategies tailored to well-defined categories of patients with different risks of treatment failure; (iii) the peculiar neoplastic tissue architecture in Hodgkin's lymphoma, which differs from that in more common subtypes of lymphoma such as diffuse large B-cell lymphoma and follicular lymphoma; and (iv) the marked chemosensitivity and radiosensitivity of the tumor.…”
mentioning
confidence: 99%
“…3 Hodgkin's lymphoma is a curable neoplasm given that, after a minimum follow-up of 6 years, more than 90% of patients are still alive and 80% are considered cured. 4 These rewarding results have been obtained by a combination of factors influencing treatment outcome in different ways. These factors can be briefly summarized as: (i) increasing accuracy of staging procedures; (ii) different treatment strategies tailored to well-defined categories of patients with different risks of treatment failure; (iii) the peculiar neoplastic tissue architecture in Hodgkin's lymphoma, which differs from that in more common subtypes of lymphoma such as diffuse large B-cell lymphoma and follicular lymphoma; and (iv) the marked chemosensitivity and radiosensitivity of the tumor.…”
mentioning
confidence: 99%
“…Before 1990, Bower et al reported an incidence of PML among patients with LPDs of 0.52% (5 cases in treatment in the 1990s has brought a dramatic reduction in failure and subsequent progression of disease [53]. Another explanation could be that the association between Hodgkin disease and PML is already well known and therefore not worth reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, treatment options of HL are tailored to type, stage, patient age, and an assessment of the risk of resistance (Diehl et al, 2003;Klimm et al, 2005). The induction chemotherapy regimens given as the initial treatment for HL are shown in Table 3.…”
Section: Chemotherapy For Early-stage Chlmentioning
confidence: 99%